2014
DOI: 10.1590/s2175-78602014000100006
|View full text |Cite
|
Sign up to set email alerts
|

Variações na riqueza e na diversidade de espécies arbustivas e arbóreas no período de 14 anos em uma Floresta de Vale, Mato Grosso, Brasil

Abstract: O presente trabalho teve como objetivo descrever variações na riqueza, na diversidade e na contribuição dos grupos ecológicos para a composição florística da vegetação arbustiva e arbórea (DAP > 5 cm) na Floresta de Vale no Véu de Noiva (FVVN), localizada no Parque Nacional da Chapada dos Guimarães, Mato Grosso, Brasil, num período de 14 anos, com base em cinco inventários (1996, 1999, 2003, 2006 e 2010). Todas as espécies arbustivas e arbóreas (DAP > 5 cm) foram amostradas sistematicamente em 18 parcela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
1
10
1
3
Order By: Relevance
“…The S values in all three surveys were intermediate in relation to other seasonal semideciduous forest with known fire occurrences; Peixoto et al (2012) reported from 148 to 168 species, while Abreu, Pinto and Mews (2014) reported from 102 to 100 species under similar conditions, and the latter group was unable to identify alterations in the forest community after a fire event (as was seen in the present study).…”
Section: Discussioncontrasting
confidence: 73%
“…The S values in all three surveys were intermediate in relation to other seasonal semideciduous forest with known fire occurrences; Peixoto et al (2012) reported from 148 to 168 species, while Abreu, Pinto and Mews (2014) reported from 102 to 100 species under similar conditions, and the latter group was unable to identify alterations in the forest community after a fire event (as was seen in the present study).…”
Section: Discussioncontrasting
confidence: 73%
“…Regarding the number of species, the three groups had a forest-like pattern, with greater CL richness, followed by CS and P. Similar results were reported by Scipioni et al (2013) and Callegaro et al (2014) in the same forest type, where light-demanding climactic species retained larger proportions of individuals and species. The higher floristic representativity of these species was also observed by Abreu et al (2014), in a Semi-Deciduous Seasonal Forest located in the Chapada dos Guimarães National Park, who attributed this condition to canopy discontinuity due to the valley's rugged relief.…”
Section: Resultssupporting
confidence: 54%
“…Pioneer species are those whose seeds germinate only in clearings and totally open canopies and receive direct solar radiation, and thereby the seedlings grow rapidly. In climax species, the seeds germinate in shaded areas and the seedling show moderate and slow growth Secondary data reported by Abreu et al (2014), Carvalho (2006), Lorenzi (2002, and Ressel et al (2004) were also used in this classification process.…”
Section: Methodsmentioning
confidence: 99%